Penerapan Partial Credit Model (PCM) dalam Mengevaluasi Tes Uraian: Application of Partial Credit Model (PCM) in Evaluating the Essay Tes - Ni Kadek Rini Purwati; I Wayan Sumandya (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
The study, titled "Application of Partial Credit Model (PCM) in Evaluating the Essay Test" aims to find out how the Partial Credit Model (PCM) is applied in evaluating tests. This research is an explorative descriptive research and data analysis is done using PCM with the help of Parscale software. Research data obtained from the results of the middle tests of numerical method. The application of PCM in evaluating the essay test provided information that the variable ability of test participants significantly influenced to the probability of correct answer, ie 98.1%, the average of the difficulty level was -0.078 indicating that the numerical method test included in the difficult category, the average ability of the test participants was -0.008 indicating that the average ability of the participants in answering the numerical methods test was in the medium category, and based on the information function and the Standard Error of Measurement (SEM) it was found that the numerical method test developed was suitable for students with the ability to medium category.